2019
DOI: 10.3748/wjg.v25.i34.5174
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Mallory-Weiss Tear during endoscopic submucosal dissection of superficial esophageal neoplasms

Abstract: BACKGROUNDAdverse events during endoscopic submucosal dissection (ESD) of superficial esophageal neoplasms, such as perforation and bleeding, have been well-documented. However, the Mallory-Weiss Tear (MWT) during esophageal ESD remains under investigation.AIMTo investigate the incidence and risk factors of the MWT during esophageal ESD.METHODSFrom June 2014 to July 2017, patients with superficial esophageal neoplasms who received ESD in our institution were retrospectively analyzed. The clinicopathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Endoscopic submucosal dissection (ESD) has been widely accepted as an effective and minimally invasive treatment for superficial esophageal neoplasms. Mallory-Weiss tear (MWT) during esophageal ESD has been recognized as a possible complication, with an approximate incidence of 5.4 % according to Chen et al [1] Here, we report a very rare case in which Mallory-Weiss tear led to severe gastric perforation during esophageal ESD. An 82-year-old man was admitted for treatment of a circumferential superficial esophageal neoplasm (▶ Fig.…”
mentioning
confidence: 72%
“…Endoscopic submucosal dissection (ESD) has been widely accepted as an effective and minimally invasive treatment for superficial esophageal neoplasms. Mallory-Weiss tear (MWT) during esophageal ESD has been recognized as a possible complication, with an approximate incidence of 5.4 % according to Chen et al [1] Here, we report a very rare case in which Mallory-Weiss tear led to severe gastric perforation during esophageal ESD. An 82-year-old man was admitted for treatment of a circumferential superficial esophageal neoplasm (▶ Fig.…”
mentioning
confidence: 72%
“…In the majority of cases, the disease arises as an upper gastrointestinal bleeding episode that generally stops spontaneously within 48 h[ 3 , 8 , 9 ]. In occasional cases, the hemorrhage requires endoscopic or surgical hemostasis[ 7 ]. Hiatal hernia, chronic nonsteroidal anti-inflammatory drug abuse, hyperemesis gravidarum, or repeated abdominal efforts are usually the more frequent predisposing factors, even if this condition may also appear in absence of any other pathology[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MWS should be suspected when a hematemesis occurs during a vomiting episode in a patient without cirrhosis. Diagnosis is made by upper gastrointestinal endoscopy, which also presents the opportunity for convenient management of any active bleeding[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 In our case, multiple lacerations also occurred at the lesser curvature of the gastric upper body and fornix. Chen et al 7 reported 20 cases (5.4%) of MWT detected during an esophageal ESD under general anesthesia, with only one case of MWT perforation. In addition, female sex and procedure time longer than 88.5 min were shown to be independent risk factors (odds ratio = 5.270 and 3.953, respectively) for MWT during esophageal ESD.…”
Section: Discussionmentioning
confidence: 99%